(AL)’s Process from Mythology to Language - Ghawadreh, Motasim Basim (Journal of Humanities & Social Sciences, 2023)
As the title indicates, this research has examined the Flectional affix, which hardly a name is devoid of. It is (Al), in order to identify how it reached the language, Based on her first religious biography, and her legendary roots, which refer back to (Eil), the great unifying god of the ancient peoples. It traces the Mythological beginning of (Al)’s Affixation and the evolution of the word (Eil) into Allah.The search finds:1- That (Al) definition began its religious life, then entered the language in the form of an adhesive, which tends to define names and remove denunciations from them, but it has until now retained some of its religious meanings.2- The word (God) was derived - linguistically - from the form (god), which religiously dates back to the word of the Great God (Eil) in ancient thought.3- The (Al) in the word majesty is derived from the monotheistic god “el”, and this is confirmed by their association with the letter (L).4- That (the) definition occupied a place at the beginning of linguistic words; Based on her religious origin (EIL), which gave her the power to occupy that place.The research recommends reconsidering the general terms that have reached us in the language dictionaries, by returning them to their religious and mythological origins, from which they emerged.
Keywords: (Al); Mythology and Language